The Mysterio framework for developing cooperative Multi-UAV Systems - Cavalcante, Antônio Sávio Nascimento; França, Breno Bernard Nicolau de (Anais do Simpósio Brasileiro de Componentes, Arquiteturas e Reutilização de Software (SBCARS); 2022: Anais do XVI Simpósio Brasileiro de Componentes, Arquiteturas e Reutilização de Software, 2022)
Over the years, UAVs (also known as drones) have been growing in studies and applications to solve diverse problems. Due to the complexity of these problems, dealing with just one UAV may not be enough, but using several UAVs together to work cooperatively increases its capacities, thus boosting solutions. However, developing cooperative Multi-UAV systems is not trivial, and reuse support is usually limited to low-level implementation. This work presents a framework for Multi-UAVs, called Mysterio, which provides an underlying software architecture with essential Multi-UAV components, enabling the reuse of design and code so that engineers can instantiate it to carry out specific missions by making UAVs work in cooperation. We also present four instances of the framework to evaluate Mysterio’s effectiveness in the face of the developed scenarios. Finally, we discuss the framework’s potential to provide and support reuse code to develop Cooperative Multi-UAVs systems for different application scenarios.